Antimicrobial stewardship programs in solid‐organ transplant recipients in Switzerland. Issue 5 (18th October 2022) - Bielicki, Julia A.; Manuel, Oriol; ,
Abstract: Introduction: Antimicrobial stewardship programs (ASPs) are essential for minimizing the emergence of antimicrobial resistance, while improving patient outcomes. The current status of ASP in the field of organ transplantation in Switzerland has not been well characterized. Methods: We describe in this article the current status of ASP and discuss challenges and opportunities of implementing ASP dedicated to solid‐organ transplant (SOT) recipients in Switzerland. Results: ASP have been implemented in the Swiss healthcare system over the last years, although specific strategies for SOT recipients are mostly based on transplant infectious diseases (TID) consultations rather than structured institutional interventions. Even so, there is a unique opportunity for developing a successful ASP in Switzerland that also specifically addresses areas of practice relevant to SOT recipients. This is due to the existent network of TID specialists in close collaboration with transplant physicians, the small number of centers involved in the care of transplant recipients, and the development of the Swiss Transplant Cohort Study (STCS), a prospective nationwide cohort of SOT recipients in Switzerland. The STCS can identify actual challenges through the updated reports on the epidemiology on transplant infections, accurately monitor the impact of potential antimicrobial stewardship interventions, and represent an opportunity for nesting of pragmatic randomized controlled trials to address key questions about optimized antibiotic use for SOT recipients. Conclusions: Although ASP in SOT recipients rely more on specific TID consultations than in general antimicrobial stewardship teams, we identified several opportunities for the implementation of a successful ASP in Switzerland. Abstract : Graphical abstract :